The use of novel diffuse optical spectroscopies for improved neuromonitoring during neonatal cardiac surgery requiring antegrade cerebral perfusion - Shaw, Kalil; Mavroudis, Constantine D.; Ko, Tiffany S.; Jahnavi, Jharna; Jacobwitz, Marin; Ranieri, Nicolina; Forti, Rodrigo M.; Melchior, Richard W.; Baker, Wesley B.; Yodh, Arjun G.; Licht, Daniel J.; Nicolson, Susan C.; et al. (Frontiers in Pediatrics, 2023)
Background: Aortic arch reconstruction presents unique challenges to maintaining cerebral perfusion, and optimal neuroprotective strategies are not completely understood. The use of antegrade cerebral perfusion (ACP) has gained favor over the more traditional deep hypothermic circulatory arrest (DHCA) due to the ability to selectively perfuse the brain. Despite this theoretical advantage, there has not been conclusive evidence that ACP is superior. One potential reason for this is the incomplete understanding of ideal ACP flow rates to prevent both ischemia from underflowing and hyperemia and cerebral edema from overflowing. Critically, there are no continuous, noninvasive measurements of cerebral blood flow (CBF) and cerebral oxygenation (StO2) to guide ACP flow rates and help develop standard clinical practices. The purpose of this study is to demonstrate the feasibility of using noninvasive, diffuse optical spectroscopy measurements of CBF and cerebral oxygenation during the conduct of ACP in human neonates undergoing the Norwood procedure. Methods: Four neonates underwent the Norwood procedure with continuous intraoperative monitoring of CBF and StO2 using two non-invasive optical techniques, namely diffuse correlation spectroscopy (DCS) and frequency-domain diffuse optical spectroscopy (FD-DOS). Changes in CBF and StO2 due to ACP were calculated by comparing these parameters during a stable 5-minute period of ACP to the last 5 minutes of full-body CPB immediately prior to ACP initiation. Results: During ACP, the continuous optical monitoring demonstrated a median (IQR) percent change in CBF of -43.4% (38.6) and a median (IQR) absolute change in StO2 of -3.63% (12.31) compared to a baseline period during full-body cardiopulmonary bypass (CPB). The four subjects demonstrated varying responses in StO2 due to ACP. ACP flow rates of 30 mL/kg/min and 40 mL/kg/min (n=3) were associated with decreased CBF during ACP compared to full-body CPB. Conversely, one subject with a higher flow rate of 50 mL/kg/min demonstrated increased CBF and StO2 during ACP. Conclusions: This feasibility study demonstrates that novel diffuse optical technologies can be utilized for improved neuromonitoring in neonates undergoing cardiac surgery where ACP is utilized. Future studies are needed to correlate these findings with neurological outcomes to inform best practices during ACP in these high-risk neonates.